ANALISIS PRINSIP MURABAHAH DALAM PENETAPAN HARGA JUAL DAN LABA - Saputri, Lestary; Sulfian, A. Sultan (IAIN BONE, 2024)
Abstract This research examines how Islamic law reviews the murabahah principle in determining the selling price and profit. This study aims to find out how Islamic law reviews the murabahah principle in determining the selling price and profit associated with transaction practices that occur in the community which sometimes do not meet the requirements of the Murabahah principle / contract. This study is a literature research using a qualitative descriptive method carried out by analyzing Islamic legal sources or other legal materials related to the murabahah principle in determining the selling price and profit. The results of this study illustrate that in the review of Islamic law based on the Quran, Prophetic Hadith, and Ijtihad of the Ulama state that basically the murabahah principle in determining the selling price and profit is valid while still paying attention to the pillars and conditions that have been determined, carried out with consensus or agreement of the parties, does not contain elements that harm one of the parties, and there is clarity and transparency in conducting transactions. As for the factors that make the principle of murabahah in determining the selling price and profit determination forbidden if the pillars and conditions of murabahah itself are not fulfilled, the taking of assets is not correct, contains elements that harm one of the parties, is not clear and transparent in the transaction, and contains elements prohibited by Shara' such as, riba (additional), gharar (uncertainty), maisir (gambling) and bathil (injustice). Abstrak Penelitian ini mengkaji bagaimana tinjauan hukum Islam terhadap prinsip murabahah dalam penetapan harga jual dan laba. Penelitian ini bertujuan untuk mengetahui bagaimana tinjauan hukum Islam terhadap prinsip murabahah dalam penetapan harga jual dan laba dikaitkan dengan praktik transaksi yang terjadi di tengah masyarakat yang terkadang tidak memenuhi syarat dari prinsip/ akad Murabahah tersebut. Studi ini merupakan penelitian pustaka dengan menggunakan metode deskriptif kualitatif yang dilakukan dengan menganalisa sumber hukum Islam ataupun bahan hukum lainnya yang berkaitan dengan prinsip murabahah dalam penetapan harga jual dan laba. Hasil dari penelitian ini menggambarkan bahwa dalam tinjauan hukum Islam yang berlandaskan pada Al- Qur’an, Hadits Nabi, serta Ijtihad para Ulama menyatakan bahwa pada dasarnya prinsip murabahah dalam penetapan harga jual dan laba adalah sah dengan tetap memperhatikan rukun dan syarat yang telah ditetapkan, dilakukan dengan konsensus atau kesepakatan para pihak, tidak mengandung unsur yang merugikan salah satu pihak, serta adanya kejelasan dan transparansi dalam melakukan transaksi. Adapun faktor yang membuat prinsip murabahah dalam penetapan harga jual maupun penetapan laba diharamkan apabila rukun dan syarat murabahah itu sendiri tidak terpenuhi, pengambilan harta yang dilakukan tidak benar, mengandung unsur yang merugikan salah satu pihak, tidak jelas dan transparan dalam transaksi, serta mengandung unsur-unsur yang dilarang oleh syara’ seperti, riba (tambahan), gharar (ketidakjelasan), maisir (perjudian), dan bathil (ketidakadilan).